Summary: 2024 EFT World Summit - Tatjana Rytsareva; Ayna Aydyn Kaykafsly; Jannatte Mussaeva (Психология и Психотерапия Семьи)
n June 2024 EFT World Summit in Haarlem, the Netherlands. It was the first time when it took place in Europe and brought together about 1,100 mental health professionals from 53 countries. Important topics as integrating cultural identity into therapy, using scientific data to improve the effectiveness of psychotherapeutic practice, and introducing innovative methods to improve emotional connections in relationships were discussed. Hope in an uncertain world - this was the main theme of the summit.